Veríssimo, critic of symbolism (1899-1901) - Simões Junior, Alvaro Santos (Revista do Instituto de Estudos Brasileiros, 2022)
From 1899 to 1901, José Veríssimo worked as the titular literary critic of the newspapers Jornal do Commercio e Correio da Manhã, both from Rio de Janeiro. By writing reviews about the literary releases of the turn of the century, Veríssimo had the opportunity to evaluate books of symbolist poetry published by disciples or admirers of Cruz e Sousa. The analysis of reviews of symbolist books intends to demonstrate briefly that the critic from Pará took these opportunities to evaluate directly or indirectly the work of the black poet.